Confinement physics of helical plasmas versus tokamaks - Yamazaki, K.; Kikuchi, M. (Вопросы атомной науки и техники, 2002)
The comparative studies of plasma confinement properties of helical and tokamak systems are carried out. Global core confinement scaling laws of both systems are similar and gyro-Bohm-like. However, local transport process is different due to inherent transport barrier and neoclassical helical ripple transport loss. As for stability limits, achievable beta in tokamak is explained by ideal or resistive MHD theories. On the other hand, beta values obtained so far in helical systems are beyond ideal Mercier mode limits. Density limits in tokamaks are often related to the coupling between radiation collapse and disruptive MHD instabilities, but the slow radiation collapse is dominant in the helical system. The pulse length of both tokamak and helical systems is on the order of hours in small machines, and the longer-pulsed good-confinement plasma operations compatible with radiative divertors are anticipated in both systems in the future. For a future advanced reactor, both tokamak and helical systems should be complementary developed.